Glutaraldehyde fixation preserves the trend of elasticity alterations for endothelial cells exposed to TNF‐α. Issue 3 (21st April 2015) - Targosz‐Korecka, Marta; Daniel Brzezinka, Grzegorz; Danilkiewicz, Joanna; Rajfur, Zenon; Szymonski, Marek
<x xml:space="preserve">Abstract</x> Among the users of atomic force microscopy based techniques, there is an ongoing discussion, whether cell elasticity measurements performed on fixed cells could be used for determination of the relative elasticity changes of the native (unfixed) cells subjected to physiologically active external agents. In this article, we present a case, for which the legitimacy of cell fixation for elasticity measurements is justified. We provide an evidence that the alterations of cell elasticity triggered by tumor necrosis factor alpha (TNF‐α) in EA.hy926 endothelial cells are preserved after glutaraldehyde (GA) fixation. The value of post‐fixation elasticity parameter is a product of the elasticity parameter obtained for living cells and a constant value, dependent on the GA concentration. The modification of the initial value of elasticity parameter caused by remodeling of the cortical actin cytoskeleton is reflected in the elasticity measurements performed on fixed cells. Thus, such fixation procedure may be particularly helpful for experiments, where the influence of an external agent on the cell cortex should be assessed and AFM measurements of living cells are problematic or better statistics is needed. © 2015 Wiley Periodicals, Inc.